An Enhanced Understanding of Culture-Negative Periprosthetic Joint Infection with Next-Generation Sequencing: A Multicenter Study. (7th September 2022) - Goswami, Karan; Clarkson, Samuel; Phillips, Caleb D.; Dennis, Douglas A.; Klatt, Brian A.; O'Malley, Michael J.; Smith, Eric L.; Gililland, Jeremy M.; Pelt, Christopher E.; Peters, Christopher L.; Malkani, Arthur L.; Palumbo, Brian T.; et al.
Abstract : Background: The challenges of culture-negative periprosthetic joint infection (PJI) have led to the emergence of molecular methods of pathogen identification, including next-generation sequencing (NGS). While its increased sensitivity compared with traditional culture techniques is well documented, it is not fully known which organisms could be expected to be detected with use of NGS. The aim of this study was to describe the NGS profile of culture-negative PJI. Methods: Patients undergoing revision hip or knee arthroplasty from June 2016 to August 2020 at 14 institutions were prospectively recruited. Patients meeting International Consensus Meeting (ICM) criteria for PJI were included in this study. Intraoperative samples were obtained and concurrently sent for both routine culture and NGS. Patients for whom NGS was positive and standard culture was negative were included in our analysis. Results: The overall cohort included 301 patients who met the ICM criteria for PJI. Of these patients, 85 (28.2%) were culture-negative. A pathogen could be identified by NGS in 56 (65.9%) of these culture-negative patients. Seventeen species were identified as common based on a study-wide incidence threshold of 5%. NGS revealed a polymicrobial infection in 91.1% of culture-negative PJI cases, with the set of common species contributing to 82.4% of polymicrobial profiles. Escherichia coli, Cutibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus ranked highest in terms of incidence and study-wide mean relative abundance and were most frequently the dominant organism when occurring in polymicrobial infections. Conclusions: NGS provides a more comprehensive picture of the microbial profile of infection that is often missed by traditional culture. Examining the profile of PJI in a multicenter cohort using NGS, this study demonstrated that approximately two-thirds of culture-negative PJIs had identifiable opportunistically pathogenic organisms, and furthermore, the majority of infections were polymicrobial. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.